Nutritional status, hygiene level, morbidity profile, and their effect on scholastic performance among school children in two subcenter areas of a PHC in Anekal Taluk, Karnataka, India - Sakthi Arasu; Farah Naaz Fathima; Nitya Raghu; Maria Vasnaik; Tom Mishael; Rahul D'Souza; Twinkle Agrawal (Wolters Kluwer Medknow Publications, 2019)
Background: Various factors such as age, sex, nutrition, hygiene, and morbidity impact the scholastic performance of schoolchildren. Objectives:(1) The objective of the study is to assess the hygiene level, nutritional status, morbidity profile, and scholastic performance of children attending government schools in two select subcenter areas of Karnataka and (2) to study the association of hygiene level, nutritional status, and morbidity profile with scholastic performance. Methodology: A cross-sectional study was done from July to August 2017 among children studying in the government schools of Mugalur and Kuthganahalli subcenters under Sarjapur PHC, Anekal Taluk, Bengaluru urban district. After obtaining permissions, general checkup of the students was done for morbidity pattern, and their anthropometric measurements were documented. Hygiene levels of the students were observed with a checklist to obtain scores that were grouped into good and poor. Attendance and grades were obtained from the class teacher to assess the scholastic performance. Results: Of a total 403 students studied, the mean age was 10.2 years (standard deviation: 2.87) with 51.1% girls. Nutrition status was good in 236 (58.6%) students and 262 (65%) had good hygiene. At the time of examination, 211 (53%) had at least one morbidity, with most common being dental caries (16.3%). Logistic regression showed that odds of girls having better grades is 2.4 times more when compared to boys and 2.1 times more likely in students with good hygiene. Students with good hygiene are 2.1 times more likely to have good attendance. Conclusion: Hygiene status impacts the attendance and grades of the students. Girl students had significantly better grades than the boys.